Emotional Branding in Joongla: A Marketing Communication in Indonesian Gastronomic Restaurant - Melati Aulia Rizky Fitriana; Almira Shabrina (Universitas Darussalam Gontor, 2025)
Indonesia has 3,259 indigenous cuisines and 10,900 medium to large-scale food and beverage businesses, indicating high competition. Changes in consumer behavior that increasingly prioritize experiences provide opportunities for gastronomic restaurants, such as Joongla, to strengthen brand positioning. This research aims to describe the application of emotional branding by Joongla in building brand loyalty and analyze the marketing communication strategies used to strengthen emotional branding. This research uses a qualitative case study approach, referring to Marc Gobe's emotional branding theory (2005). The results showed that Joongla successfully implemented the four dimensions of emotional branding: relationship, sensorial experience, imagination, and vision. Joongla can build long-term relationships with consumers through emotional attachment, making sensorial experience the principal value, creating consumer imagination through physical media and storytelling, and consistently communicating Joongla's vision. Emotional branding encourages consumers to return to visit and recommend it to others based on their experience. Joongla's application of emotional branding functions as a form of brand communication that builds emotional connections with consumers, strengthens brand loyalty, and encourages word of mouth. Keywords: emotional branding; marketing communication; word of mouth; brand loyalty; gastronomy